The Sensus Divinitatis and Non-Theistic Belief; or Turning Plantinga’s Religious Epistemology Against Christian Theism - Perrine, Timothy (Theology and science, 2024)
A key element of Plantinga’s religious epistemology is that de jure objections to Theistic belief succeed only if de facto objections to Theistic belief succeed. He defends that element, in part, by claiming that human beings have an innate theistic faculty, the sensus divinitatis. In this paper, I argue that Plantinga’s religious epistemology makes Christian Theism open to a de facto objection due to the characteristics and distribution of religious beliefs in the world. I defend my argument from a potential objection from skeptical theism, before concluding with a comparison to a similar argument.